(untitled) (Med Phoenix, 2018)
Background: Discharging ear is a common symptom among the patients presenting in ENT OPD for consultation. The commonest cause for discharging ear is chronic otitis media. Poverty, ignorance, crowded living conditions due to large families, poor sanitation, and lack of personal and environmental hygiene are some of the main factors behind the prevalence of chronic otitis media. National medical college and teaching hospital is a tertiary care center located in Birgunj metropolitan city in central Nepal. It caters to thousands of patients with discharging ear each year. Methods: This qualitative, descriptive study was carried out in department of ENT-HNS at National Medical College and Teaching Hospital located Birgunj-15, Parsa, Province no. 2 of Nepal for duration of one year from August 1, 2014 to July 30, 2015. Two hundred and five (205) adult patients with complains of unilateral discharging ear were included in the study. Results: Mostly female patients and those in the age group of 15-30 years from Bara and Parsa districts of Nepal including the areas around the Indo-Nepal border avail the services of department of ENT-HNS of National medical college and teaching hospital. Conclusions: The delivery of ENT-HNS services to the concerned patients is insufficient and inefficient owning to various factors. The government of Nepal and India along with National medical college and teaching hospital can work together to improve the situation. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 48-51